Comparison between the spray drying and spray chilling microparticles contain ascorbic acid in a baked product application - Alvim, Izabela Dutra; et al. (2016)
One of the functions of microencapsulation is the protection of sensitive substances. Many encapsulation methods can be employed for the same substance, and the degree of protection may vary according to the particle characteristics (i.e. dry or wet matrix, hydrophilic or hydrophobic surface, etc.). This study aimed to compare the characteristics of microparticles containing ascorbic acid (AA) by spray drying (SD; wall material: arabic gum) and spray chilling (SC; wall material: stearic acid þ hydrogenated vegetable fat) to assess the degree of protection of the microstructures formed in their application in biscuits. The microparticles obtained by the two methods showed typical spherical morphologies and high polydispersity. The average diameters were 9.3 ± 0.2 and 31.2 ± 0.7 mm for SD and SC particles, respectively. The encapsulation efficiencies were high (>97%) for both samples. In the biscuits application, both structures suitably protected the AA (preservation of more than 85% of the added content of AA) compared with the addition of the free active substance (loss of 28% of AA). The SD microparticles providing a greater protective effect than the SC microparticles. Both microencapsulation methods can be used to obtain microparticles as potential protection vehicles in the application of sensitive substances in baked products. © 2015 Elsevier Ltd. All rights reserved.